Lameness in weaned pigs associated with tetracycline overdose - Gotter, V.; Wolf, P.; Kamphues, J.; Beilage, E. Grosse (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2013)
On a piglet producing farm severe lameness was observed in pigs which had been weaned 3 weeks and longer due to severe distortions of joints and claws of fore and/or hind legs. Splaying of claws as well as flexural limb deformations particularly in the carpal joints increased in degree the older and heavier the pigs were. Because of coughing in the weaners, which had started 7–8 weeks before any lameness or limb deformation had been apparent, tetracycline was applied via water as medication. During the course of an on-site investigation, a miscalculation of dosage – 129–168 mg tetracycline per kg body weight – was revealed. It was therefore suggested to the farmer and his veterinarian to immediately stop the application of tetracycline and to use a different antibiotic against the still present coughing and sneezing. During a follow-up evaluation 4 weeks later, the farmer reported a significant decrease in affected animals. While a direct correlation between the lameness in the weaned pigs and the tetracycline dosage could not be proven, the existing evidence supports the theory that the overdosage was at least a contributing factor.
Keywords: Swine; medication; water supply; non-infectious; multi-factorial disease